Notch1 signaling impairs regulatory T cells during multisystem inflammatory syndrome in children - Magali Noval Rivas; Moshe Arditi (The Journal of Clinical Investigation, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a rare pediatric inflammatory disorder characterized by immune cell hyperactivation, cytokine storm, and the production of autoantibodies. The mechanisms underlying such immune dysregulation still need to be unraveled. In this issue of the JCI, Benamar et al. demonstrated the critical role of the Notch receptor 1/CD22 (Notch1/CD22) axis in Tregs, which, when activated, impairs Treg functions and promotes inflammation. They showed that the Notch1/CD22 axis contributed to dysregulated immune responses in MIS-C. These findings may have implications for MIS-C and many other inflammatory diseases.